Efektivitas Penerapan Sistem E-Planning Dalam Perencanaan Pembangunan di Pemerintahan Kabupaten Tapanuli Selatan - Diana Rosalina Harahap; Badaruddin Badaruddin; R. Hamdani Harahap (Universitas Medan Area, 2021)
This research raises the phenomenon of e-planning which is one of the systems and technology innovation programs in government today. The Tapanuli Selatan District through the Regional Development Planning Agency began implementing the e-planning system since 2016. It is interesting for researchers to see the development of the implementation of this e-planning system which has been running for 4 years. In this study, researchers used effectiveness theory with effectiveness measurement according to Duncan. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. Meanwhile, data analysis techniques use data reduction, data presentation, and drawing conclusions. During this research, the researcher found data that the Tapanuli Selatan District, in this case BAPPEDA, was still not effective in implementing the e-planning system because it did not meet the variables that Duncan required. The unfulfilled variables are goal achievement and adaptation. Meanwhile, the fulfilled variable is integration. With this research, it is hoped that it can become a reference for the Tapanuli Selatan District to improve the implementation of the e-planning system so that it can fulfill all the requirements stated in the Duncan effectiveness measurement.